A Study on Customer Satisfaction towards Online Shopping in Nepal - Rai, Pushpa; Kadariya, Madan (Journal of Science and Technology, 2024)
Online shopping is a new method of purchasing that is growing quickly in Nepal because of the emergence of the Internet. The expanding popularity of internet shopping in Nepal presents a chance to broaden and expand the business. This study aims to examine the relationship between independent variables namely Reasonable Product Price, Product Delivery, Product Quality and Product Return Policy with dependent variable namely customer satisfaction towards online shopping in Nepal. A survey method with standard questionnaire was used for data collection. A total of 499 respondents from Nepal responded to the survey. Among them 415 are respondents who have done online shopping and rest 84 haven’t done online shopping because of various reason. Since the study focus on customer satisfaction towards online shopping, responses from 415 respondents are consider for further study. The findings revealed reasonable product price, product delivery, product quality and product return policy have positive relationship with customer satisfaction in Nepal. Result of the study also shows that product price most affect the customer satisfaction among four variables. This study provides with valuable insights and guidance on customers’ satisfaction, leading to increased revenue and customer.